2011
DOI: 10.1097/qmh.0b013e3182033791
|View full text |Cite
|
Sign up to set email alerts
|

A Healthcare Lean Six Sigma System for Postanesthesia Care Unit Workflow Improvement

Abstract: The full benefits of the new model will be realized when applied at both strategic and operational levels. For further research, we will examine how the proposed model is used in different real-world case studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 11 publications
0
18
0
2
Order By: Relevance
“…Besides the above-discussed strategic planning methods, this paper, based on a study [79], proposes a health care cloud computing strategic planning (HC 2 SP) model that can be used by a health organization to determine its direction, strategy, and resource allocation to migrate from traditional health services to cloud-based services. The model includes 4 stages: identification, evaluation, action, and follow-up (see Figure 2).…”
Section: Cloud Computing Strategic Planningmentioning
confidence: 99%
“…Besides the above-discussed strategic planning methods, this paper, based on a study [79], proposes a health care cloud computing strategic planning (HC 2 SP) model that can be used by a health organization to determine its direction, strategy, and resource allocation to migrate from traditional health services to cloud-based services. The model includes 4 stages: identification, evaluation, action, and follow-up (see Figure 2).…”
Section: Cloud Computing Strategic Planningmentioning
confidence: 99%
“…However, application of HLM stimulates discussion about how to solve system and process issues and improve quality and patient safety 22,60,68,74. Most of the analyzed papers have underscored the limits of HLM and barriers to its implementation,9,21,31,32,39,52,54,56,57,60,62,63,65,66,68,78 demonstrating that HLM can not be successfully implemented without considering the proper critical factors and precautions highlighted in the previous section of this paper.…”
Section: Resultsmentioning
confidence: 99%
“…This score helps to find out critical failure modes and evaluates the risk related with the procedure [16] Baddour AA et al, conducted a study to reduce the incidence of needle stick injuries in healthcare workers utilising six sigma methodolgy and concluded this strategy as an effective method in cause reduction [3]. Kuo AM et al, carried out a study using six sigma system for postanaesthesia care unit workflow improvement and revealed that the new method decreased and improved the service gaps between health care providers and patients as well as balanced the requirements of health care managers and delivered health care services to patients by utilizing the six sigma high-quality principles [17]. Karen R et al, initiated a Cancer Service Line Patient Flow Project using the DMAIC process of Six Sigma to improve patient flow and reduce delays and found that before the initiation of project, 29% of the treatments started within 22 minutes, however after implementing the changes, this increased to 78% [18].…”
Section: Discussionmentioning
confidence: 99%